PENDIDIKAN MORAL KIDS ZAMAN NOW DALAM PERSPEKTIF ISLAM - Syukron, Akhmad Aufa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This paper seeks to photograph the thinking of moral education of children today in the perspective of Islam, the term children nowadays in IndonesianÂ better known as Kids Zaman Now. Kids Zaman Now is actually a joke as well as satire refers to the